Anatomical and Histological Characteristics of Gonad of Tropical Eel Anguilla bicolor McClelland, 1844 in Different Length Body Size - Farida Nur Rachmawati; Ridwan Affandi; Yulia Sistina (Universitas Gadjah Mada, 2022)
The sex status of Anguilla bicolor McClelland is difficult to be distinguished between males and females. Thus, we evaluated 309 fishes from The Serayu River, with length and weight range around 9 - 81 cm and 0.59 - 1260 g respectively to access the anatomical and histological characteristics of their gonads for each sex. Parameters assessed were body sizes, eye diameter, fin length, and gonad weight. The results showed that body length, weight, eye index, and gonadosomatic index of the male were significantly smaller (p<0.01) than those of the females. Fins index was not significantly different (p>0.05) between males and females. The histological structure of gonad showed that the eel gonads can be classified as either indifferent gonads, testis, or ovary based on the length of body size. Collecting all the data together it can be concluded that A. bicolor is a gonochoric.